The Development of the Perth Charter for the Promotion of Mental Health and Wellbeing - Anwar McHenry, Julia; Donovan, Robert (The Clifford Beers Foundation, 2013)
The Perth Charter for the Promotion of Mental Health and Wellbeing is an initiative of the organizing committee of the 7th World Conference on the Promotion of Mental Health and Prevention of Mental and Behavioural Disorders. An iterative feedback process was used to develop and revise the charter principles in consultation with health professionals. A final online survey showed strong support for each of the eight principles, which were rated ‘essential’ (as distinct from ‘desirable’ or ‘not relevant’) by 73–96% of respondents. The principles were supported most strongly by practitioners, of whom 85–100% classified each as ‘essential’. It is hoped that mental health professionals find the Charter useful for advocating for greater resource allocation in their jurisdictions to mental health, in general and to mental health promotion in particular.